(untitled) (Indian Journal of Child Health, 2018)
Scimitar syndrome is a congenital anomaly characterized by anomalous drainage of the right lung into inferior vena cava. This may be associated with other anomalies in the form of pulmonary hypoplasia, systemic arterial supply of right lung, and congenital heart diseases. We report an infant with recurrent pneumonia who turned out to be a case of scimitar syndrome on further workup. The patient was managed surgically by selective embolization of the artery from celiac trunk to sequestered lung. This case report highlights the fact that scimitar syndrome should be suspected in a patient with recurrent pneumonia with typical chest X-ray findings.